An outline of the 1994-1998 European inspection and maintenance study: part I-design, tests, and results of experimental methods - Samaras, Zissis; Joumard, Robert; Hassel, Dieter; Weber, Franz Josef; Rijkeboer, Rudolf; Zachariadis, Theodoros (My University, 2001)
This paper provides an overview and the main results of a study aiming to evaluate current and alternative inspection and maintenance (I/M) programs to control emissions from in-use cars in Europe. For this purpose, a large number of passenger cars from five countries (France, Germany, Greece, the Netherlands, and the United Kingdom) were tested according to a common test protocol that included a variety of driving cycles and short tests, both legislative and specifically developed for this exercise. Evaluation of all test results was conducted with the objective of defining effective I/M test procedures and examining the potential of periodic I/M programs to reduce pollutant emissions and improve fuel economy of in-use cars. The results indicate that the current idle test used for catalyst-equipped cars in Europe is probably ineffective, while short An Outline of the 1994–1998 European Inspection and Maintenance Study: Part I—Design, Tests, and Results of Experimental Methods Zissis Samaras and Theodoros Zachariadis Aristotle University of Thessaloniki, Greece Robert Joumard French National Institute for Transport and Safety Research, Bron Cedex, France Dieter Hassel and Franz-Josef Weber Technischer Überwachungsverein Rheinland, Cologne, Germany Rudolf Rijkeboer Netherlands Organization for Applied Scientific Research, Delft, The Netherlands transient loaded testing was found to offer higher potential in environmental terms. Regarding conventional gasoline cars, it is concluded that the idle test is sufficient, provided that the CO cut point is reduced and an HC test is added at high idle. Finally, the effectiveness of the free acceleration smoke test for diesels is questioned, while a transient cycle with continuous opacity measurement was found to be very promising. A companion paper further uses these results to analyze the likely cost-effectiveness on a per-country basis and discusses the possible effect of maintenance on emissions.